3D Laser Engineering of Molten Core Optical Fibers: Toward a New Generation of Harsh Environment Sensing Devices. Issue 18 (30th June 2022) - Wang, Yitao; Cavillon, Maxime; Ballato, John; Hawkins, Thomas; Elsmann, Tino; Rothhardt, Manfred; Desmarchelier, Rudy; Laffont, Guillaume; Poumellec, Bertrand; Lancry, Matthieu
Abstract: Aluminosilicate glasses offer wide‐ranging potential as enabling materials for a new generation of optical devices operating in harsh environments. In this work, a nonconventional manufacturing process, the molten core method, is employed to fabricate and study sapphire (Al2 O3 ) and YAG (yttrium aluminum garnet) derived all‐glass silicate optical fibers in which a femtosecond (fs) laser is used to imprint oriented nanostructures inside the fiber cores. Both writing kinetics and thermal stability of the laser‐modified regions are investigated over a wide temperature range (20–1200 °C). The laser‐imprinted modifications in these high alumina‐content fibers exhibit improved thermal stability with respect to commercial pure silica and GeO2 ‐doped silica analogs. Furthermore, optical devices in the form of Rayleigh backscattering and fiber Bragg grating sensors are fabricated to demonstrate the high‐temperature sensitivity and stability of these nonconventional fibers. This functionalization of aluminosilicate fibers by fs‐laser direct writing opens the door to a new generation of optical devices suitable for high‐temperature operation. Abstract : This work combines femtosecond laser direct writing (FLDW) with a nonconventional optical fiber fabrication technique called the molten core method (MCM), to 3D inscribe thermally stable nanostructures in glass optical fibers. This materials‐driven approach is validated through the fabrication of temperature sensors, opening the door to a new generation of optical fiber‐based devices operating in high‐temperature environments.